(untitled) (Journal of Engineering, 2019)
The weather of Iraq has longer summer season compared with other countries. The ambient temperature during this season reaches over 50 OC which makes the evaporative cooling system suitable for this climate. In present work, the two-stage evaporative cooling system is studied. The first stage is indirect evaporative cooling (IEC) represented by two heat exchangers with the groundwater flow rate (5 L/min). The second stage is direct evaporative cooling (DEC) which represents three pads with groundwater flow rates of (4.5 L/min). The experimental work was conducted in July, August, September, and October in Baghdad. Results showed that overall evaporative efficiency of the system (two coils with three pads each pad of 3cm) reach to 167 % with the temperature difference between ambient and supply is 26.2oC. While it reached 122.7% (one coil with three pads ) with the temperature difference between ambient and supply is 16OC and reduced to 84.88% and 84.36% for IEC and DEC respectively.